The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/psyp.12073
|View full text |Cite
|
Sign up to set email alerts
|

Learning‐induced modulations of the stimulus‐preceding negativity

Abstract: The neural basis of feedback expectation, which is crucial in learning theory, has only been minimally studied. Stimulus-preceding negativity (SPN), an ERP component that appears prior to the presentation of feedback, has been proposed as being related to feedback expectation. The present study showed, for the first time, amplitude modulations of the SPN component during learning acquisition in a trial-by-trial associative learning task. The results indicate that SPN could be a plausible electrophysiological i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
69
4
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 49 publications
18
69
4
6
Order By: Relevance
“…This correlation was still present when both groups were analyzed separately: High ET (r = -0.5, p = .035); Low ET (r = -0.57, p = .014). This association observed is in agreement with the idea that the larger the expectancy towards external feedback, the larger the motivational impact of its presentation (Fuentemilla et al, 2013;Moris et al, 2013). …”
Section: Anticipation and Processing Of Positive Feedbacksupporting
confidence: 81%
See 4 more Smart Citations
“…This correlation was still present when both groups were analyzed separately: High ET (r = -0.5, p = .035); Low ET (r = -0.57, p = .014). This association observed is in agreement with the idea that the larger the expectancy towards external feedback, the larger the motivational impact of its presentation (Fuentemilla et al, 2013;Moris et al, 2013). …”
Section: Anticipation and Processing Of Positive Feedbacksupporting
confidence: 81%
“…The SPN amplitude was modulated by the relevance of the feedback, main effect of error feedback type, F(2, 68) = 24.6, p < .001, ηp 2 = 0.42, being greater during Final reversal errors (FRE) when compared to Spurious negative and Reversal trials. In agreement with previous studies (Masaki et al, 2006;Moris et al, 2013), the SPN increase during motivationally engaging and relevant feedback (in this case, Final reversal errors) was greater during the time window of 200 to 0 ms preceding feedback onset as revealed by the interaction error feedback type x time, F(2, 68) = 11.2, p < .001, ηp 2 = 0.25. A triple interaction error feedback type x time x Group, F(2, 68) = 4.6, p < .05, ηp 2 = 0.12, further showed that during the 200 ms preceding feedback presentation the enhancement of the SPN amplitude during Final reversal errors was stronger on the High ET group.…”
Section: Anticipation Of Negative Error Feedback: Spnsupporting
confidence: 77%
See 3 more Smart Citations